Bond Behavior between BFRP Rebar and Seawater Sea Sand Concrete. (25th September 2020) - Wu, Chao; Meng, Bing-Chen; Cheng, Xianfeng; Korayem, Asghar Habibnejad; Tam, Lik-Ho
Abstract : Seawater sea sand concrete (SWSSC) is a promising alternative to ordinary concrete in terms of saving valuable natural resources of freshwater and river sand. Basalt fiber reinforced polymer (BFRP) rebars can be a good solution to corrosion of steel rebars in SWSSC. This paper presents an experimental study on the bond behavior between SWSSC and BFRP rebars through pullout testing. Concrete mixed with freshwater and river sand was also prepared for comparison with SWSSC. BFRP rebars with two different surface configurations were selected, that is, ribbed surface and sand-coated surface. Fly ash as a replacement of cement was also investigated in terms of its effect on bond behavior. Failure modes, bond-slip relationships, and bond strengths were reported and discussed in terms of the previously mentioned parameters. It was found that ribbed surface of BFRP rebar could achieve better mechanical interlocking with surrounding concrete. SWSSC could have comparative bond strength with BFRP rebar compared with ordinary concrete. However, using fly ash to replace cement is not recommended because it would significantly reduce concrete strength leading to much lower bond at the interface between SWSSC and BFRP rebar.